Assessment of ankle muscle activation by muscle synergies in healthy and post-stroke gait - Ji, Qing; Wang, Fei; Zhou, Rui; Li, Jianhua; Wang, Jian; Ye, Xuesong (Physiological measurement, 2018)
Impaired ankle dorsal and plantar flexor function is a frequent sequela of stroke. A better assessment of ankle muscle activation would be highly significant for stroke rehabilitation. The challenge in implementing current electromyography (EMG)-based assessments is due to problems with the variability and individuality of ankle muscle EMG profiles during walking. We have been studying a new technique using the muscle synergy method to quantify the characteristics that underlie ankle muscle activation to address this issue. We processed surface EMG signals from ankle muscles and gait parameters collected from 20 healthy and 22 post-stroke subjects during walking. A non-negative matrix factorization algorithm was used to extract muscle synergies. Our results suggest a featured muscle synergy structure (R  =  0.84, 95% CI: 0.83-0.85) underlying ankle muscle activation in both healthy and post-stroke subjects. The structure of the featured muscle synergy was robust in the same subjects across different conditions in the healthy group (R  =  0.97, 95% CI: 0.96-0.98) and the post-stroke group (R  =  0.95, 95% CI: 0.88-0.97). Compared to the stroke group, the synergy patterns of healthy subjects showed better regularity and higher inter-subject similarity (P  =  0.001). In addition, the results of muscle synergies were indicative of locomotor performance. The innovative quantitative results of this study can help us to better understand ankle muscle activation and will be a reference for clinical assessments and intervention studies.